Holistic Academic Supervision Model for Cultural Art Teachers of Vocational High Schools - Ambarwangi, Sri; Rachman, Maman (Harmonia: Journal of Arts Research and Education, 2015)
This study is aiming at (1) describing and analyzing the current implementation of academic supervision (factual model),Â  (2) generating and analyzing academic supervision model as needed (hypothetical model), and (3) identifying and analyzing the effectiveness of a holistic model of academic supervision (the final model). The method employed in this research was the Research and Development (R&D) method, which was divided into three phases: a preliminary study, stage of development and evaluation stages. The data sources were the school superintendents, teachers, as well as students. Further, the data were collected by conducting interviews, questionnaires, and observations. Results showed that the current implementation of academic supervision was considered less effective. The academic supervision which is considered as appropriate for cultural art teachers is a holistic academic supervision. It involves school superintendents and cultural art teachers who are supervised, starting from the planning stage up to the follow-up stage, so that, a good relationship between them will be established. It is concluded in this study that a holistic academic supervision model is effective to enhance the professional competence of cultural art teachers.